Unpacking the Struggles: An Analysis of Senior High School Students’ Difficulties in Writing Argumentative Texts - Isnawati, Uzlifatul Masruroh; Novitasari, Dian (ITScience (Information Technology and Science), 2025)
This study aims to identify errors made by students in writing argumentative texts in English. The main focus of this study is to analyze the types of errors based on four assessment aspects: content, organization, language use, and vocabulary. This study used a descriptive qualitative approach, using data from 15 argumentative texts from 11th-grade students at MAN 1 Lamongan. Data analysis was conducted by examining each text based on these four aspects and then classifying the types of errors. The results showed that the most frequently encountered error aspect was language use, with a percentage of 62%, followed by content (14%), organization (13%), and vocabulary (11%). Errors found included incorrect grammar, irrelevant ideas, illogical paragraph structure, and inappropriate vocabulary. These findings indicate that students still struggle to construct logical and coherent arguments and use English accurately. This research is expected to provide teachers with considerations in providing more effective and focused writing lessons, as well as serve as a reference for further research to develop strategies to improve argumentative writing skills.